Investigation of Photo-Absorption and Current-Voltage Properties of Liquid Extracts from Fruits for Organic Solar Cells Application - Babakr, Dashty A.; Bayiz, Hamad H.; Qadr, Hawkar M.; Muhammad, Fahmi F. (Journal of Technology Innovations in Renewable Energy, 2016)
In this research work, the optical absorption and photo-current characteristics of black grape, strawberry and orange solutions were investigated. The solutions were extracted from fresh fruits and UV-V is spectrophotometer was utilized to record the absorption spectra of the samples. Besides, the photo-current properties were investigated via current-voltage characteristics of the fruit solutions under illumination. The results showed that energy gaps of the fruits are located within the visible spectrum. Energy gap of 1.84eV was found for the black grape, 2.11eV for strawberry and 3.10eV for the orange solution. The broad absorption spectra for black grape and strawberry have proved the fruits capability to harvest solar energy. Additionally, the enhanced photo-current activity of the fruit solutions under light suggested their potential application for the organic and/or dyes solar cells